CENTRO EDUCACIONAL UNIFICADO, CONTRAPOSIÇÃO À PEDAGOGIA DE LATA - Fasano, Edson (2006)
This paper, which results from a qualitative research on education, intended to reflect on the counter-hegemonic potential of the Unified Educational Center (Centro Educacional Unificado CEU) compared to neoliberal principles on education, also called Tin Pedagogy. There is a bibliographic study of the neoliberal educational policy which is compared to experiences developed by the Department of Education of São Paulo municipality in the nineties. The paper analyses the proposal of the Citizen School school that aimed to develop citizenship (Escola Cidadã) identifying its principles with those of the CEU proposal. Open interviews were conducted with protagonists of the project, in order to analyse the institution process. It was observed that the project, first counter-hegemonic, was submitted to a dialetic institution process. Afterwards it lost their characteristics under the municipal administration of São Paulo in 2005.